Compostagem de resíduos orgânicos e seus efeitos no cultivo do tomate cereja - Ferreira, Ana Kaline da Costa (Universidade Federal Rural do Semi-Árido, 2016)
Composting is a solution for recycling organic waste, transforming them into compounds that can be used as nutrients for any plant species, with emphasis on the vegetable group. The objective of the present study was to take advantage of biodegradable solid waste, making possible the production of organic fertilizers by means of the composting technique, with a view to their application in the cultivation of cherry tomatoes. The research was based on two experiments. The first was developed through an action research in the Community Association Recycling for Life, located in the municipality of Mossoró/RN. The composting technique was developed according to the windrow method, with the construction of five piles. Controlled until the final phase of composting, parameters such as: temperature, humidity, pH, total organic carbon, total nitrogen, and C/N ratio. Analyzes of humic substances, macro and micronutrients, chemical contaminants (Cd, Ni and Pb), total and thermotolerant coliforms, Salmonella, visual observations of maturation and suggestion of packaging and labeling of the organic compounds produced were performed. The second experiment was carried out in a protected environment, in the West Field of the Federal Rural Semi-Arid University - UFERSA, Mossoró/RN, in order to observe the effects of the organic compounds produced in the cultivation of cherry tomatoes. The experimental design used was in randomized blocks, with five replicates and five treatments, the organic fertilizers produced in the first experiment were combined with coconut fiber (1:1). In the culture were evaluated growth, production, post-harvest quality, nutrition and microbiological analysis.The stabilized organic compounds reached satisfactory results with C/N values between 12/1 to 16/1, presenting as good soil conditioners with potential to improve the physicochemical characteristics of a soil that presents nutritional deficiency. The levels of chemical contaminants evaluated were well below those established in the main European, American and normative legislation, showing that they are within the parameters of quality for the organic compounds that will have applications as fertilizers and soil conditioners. The compounds produced showed absence of total coliforms, thermotolerant and Salmonella. In the crop, the organic production was satisfactory to favor a product of quality free of nutritional and healthy deficiency due to the absence of pathogens. The T5 treatment presented a better result with higher phytomass and average productivity, indicating that significant and diversified amounts of food residues influence the amount of nutrients that will be available to the crop. The results allow us to affirm that the application of cattle manure and dietary residues in small scale composting originated a product with adequate nutritional characteristics and did not alter the microbiological quality of the compounds and concomitantly of the cultivated tomatoes, resulting in the production of healthy fruits. This favors the organic production system as a market potential and an economic alternative for family farmers
Composting of organic residues and their effects on the cultivation of cherry tomatoes
Keywords: Ambiente protegido; Adubação orgânica; Lycopersicum esculentum Mill; Catadores de materiais recicláveis; Sustentabilidade ambiental; Protected environment; Organic fertilization; Esculentum lycopersicum Mill; Waste pickers; Environmental sustainability; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO